Cell Growth Inhibition of Saponin XII from Dipsacus japonicus Miq. on Acute Myeloid Leukemia Cells - Cham, Ba Thi (Molecules, 2020)
In previous studies, we isolated the known compound saponin XII from the roots of Dipsacus japonicus Miq. Here, we show that this compound reduced the number of acute myeloid leukemia OCI-AML3 cells as evaluated by a hemocytometer. Flow cytometry analyses demonstrated that the reported activity was associated with a significant increase of apoptosis and of cells in the G(0)/G(1) phase of the cell cycle, with a decrease of cells in the S and G(2)/M phases. Thus, the inhibition of cell growth in OCI-AML3 cells was due to antiproliferative and pro-apoptotic effects. Interestingly, the bioactivity of saponin XII exerted its effect at a concentration as low as 1 µg/mL.